The Correlation between Elderly Behavior and Family Support for Hypertension Control in Gorontalo - Indriani Indriani (Universitas Wiralodra, 2021)
Abstract Hypertension is the first of the fifteen diseases in Gorontalo city which mostly affects the elderly, with a total of 2240 people. One of the efforts to control the risk of increased hypertension is through family support so that the elderly at the age who are no longer productive can still improve their health status. This study used an observational research design with a cross-sectional approach. Sampling in this study was carried out by means of simple random sampling with the criteria of the elderly who came for treatment at health centers and were willing to be respondents, namely as many as 33 respondents. The results showed that the correlation between family support and elderly behavior in controlling hypertension using the chi square test got a value of ρ = 0.025 <a = 0.05. The conclusion of this study is that there is a significant relationship between family support and the behavior of the elderly in controlling hypertension. Support from family can motivate the elderly to maintain their quality of life in old age.